THE EFFECT OF GOOD CORPORATE GOVERNANCE ON TAX AVOIDANCE WITH PROFITABILITY AS A MODERATING VARIABLE: EVIDENCE FROM INDONESIAN MANUFACTURING COMPANIES - Robin (CV. Radja Publika, 2025)
Purpose – This study investigates whether profitability moderates the association between Good Corporate Governance (GCG) mechanisms and tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The key argument is that GCG effectiveness in constraining tax avoidance is conditional upon firm profitability levels, as higher profitability simultaneously increases both tax avoidance incentives and political costs of non-compliance. Design/Methodology/Approach – This study analyzes 460 firm-year observations from 92 manufacturing companies selected through purposive sampling. The primary analysis employs panel data regression with firm fixed effects and year dummies using Stata 17, complemented by Moderated Regression Analysis (MRA) to test interaction effects. GCG is proxied by independent commissioners, audit committee size, institutional ownership, and external audit quality (Big Four affiliation). Tax avoidance is measured using Cash Effective Tax Rate (CETR), and profitability by Return on Assets (ROA). Robustness checks include pooled OLS, Book-Tax Difference as an alternative proxy, and split-sample analysis by profitability median. Findings – Independent commissioners (β = 0.148; p < 0.01), institutional ownership (β = 0.178; p < 0.01), and audit quality (β = 0.218; p < 0.01) are significantly positively associated with CETR indicating lower tax avoidance. Audit committee size shows no significant association (p = 0.132). Profitability significantly moderates the associations between independent commissioners (β = 0.164; p < 0.01) and institutional ownership (β = 0.142; p < 0.01) with tax avoidance, but does not moderate the audit committee and audit quality paths. Research Implications – The sample is confined to manufacturing companies, limiting cross-sector generalizability. CETR is influenced by temporary differences between accounting and taxable income. Audit quality is proxied solely by Big Four affiliation, not capturing qualitative dimensions. The observational design precludes definitive causal claims. Originality/Value – This study provides evidence consistent with profitability functioning as a moderating mechanism that explains when GCG is effective in constraining tax avoidance. The findings reveal that strategic monitoring mechanisms (independent commissioners and institutional investors) are conditionally effective depending on profitability, while procedural compliance mechanisms (audit committees and external auditors) operate more universally. The 2020–2024 period covering pandemic disruption, fiscal incentives, and the implementation of Indonesia's Tax Harmonization Law provides a unique empirical setting.